2018
DOI: 10.1155/2018/5748281
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Scatter Reduction Method in Cone-Beam Computed Tomography for Dental and Maxillofacial Applications Based on Monte Carlo Simulation

Abstract: The quality of images obtained from cone-beam computed tomography (CBCT) is important in diagnosis and treatment planning for dental and maxillofacial applications. However, X-ray scattering inside a human head is one of the main factors that cause a drop in image quality, especially in the CBCT system with a wide-angle cone-beam X-ray source and a large area detector. In this study, the X-ray scattering distribution within a standard head phantom was estimated using the Monte Carlo method based on Geant4. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Perhaps the most important and common method to evaluate and ensure a simulation results using experimental examination is to compare the intensity pattern of the pixels of simulated and simple experimental phantom images. However, in a study conducted by Thanasupsombat et al ,[ 29 ] a human-like head phantom was used. In addition, in a study by Najafi Darmian et al ,[ 36 ] GATE validation was done by comparing the scattering profile on a row detector of a CT scan between the simulation and the experimental exams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most important and common method to evaluate and ensure a simulation results using experimental examination is to compare the intensity pattern of the pixels of simulated and simple experimental phantom images. However, in a study conducted by Thanasupsombat et al ,[ 29 ] a human-like head phantom was used. In addition, in a study by Najafi Darmian et al ,[ 36 ] GATE validation was done by comparing the scattering profile on a row detector of a CT scan between the simulation and the experimental exams.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Monte Carlo technique has been highly effective due to its statistical and random nature. [ 29 , 37 , 38 ] In order to evaluate the success of GATE in scatter estimation more comprehensively, four quantities were investigated for scatter correction. The middle row, filled with water, has been chosen for pixel intensity evaluation in a uniform environment.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse results have been reported, depending on the standard used to evaluate scan devices, image quality, amount of dose reduction, and exposure parameters. Most studies have found that a substantial dose reduction using exposure parameters below the manufacturer's guidelines is possible with adequate visibility [ 24 26 ]. Rivas et al found that dose reductions to 50% lower than the manufacturer's default settings could be achieved by decreasing the X-ray tube voltage [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methods using signal processing techniques have been developed to estimate and correct for scattering effects. The scattered x-ray distribution can be predicted via Monte-Carlo (MC) simulations [26,27]. Although it is a powerful tool, the poor convergence properties of MC sampling leads to timeconsuming calculations.…”
Section: Compton Scatteringmentioning
confidence: 99%